The fast and the furious - Sampson, Edward, 1912-1987; Ireland, John, 1914-1992; Odlum, Jerome, 1905-1954; Howell, Jean; Malone, Dorothy; Palo Alto Productions; Cinetel Films ([Los Angeles, CA] : Palo Alto Productions, 1954)
John Ireland stars as escaped convict Frank Webster, a convicted murderer who is out to prove his innocence. He kidnaps Connie Adair, who is driving a tuned up muscle car to compete in a rally. She soon overcomes her fear of her captor when she realizes that he has been driven to desperate measures by circumstance. Soon they become both lovers and fugitives, hiding from the law and racing for the border under cover of the road race.
Originally released as motion picture in 1955.
John Ireland, Dorothy Malone, Bruce Carlisle, Iris Adrian, Marshall Bradford, Bruno Ve Sota, Byrd Holland, Larry Thor.
Cinematographer, Floyd Crosby; editor, Edwards Sampson; music, Alexander Gerens.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016).
Keywords: False imprisonment -- Drama; Prisons -- Drama; Kidnapping -- Drama; Hostages -- Drama; Fugitives from justice -- Drama; Man-woman relationships -- Drama; Automobile racing -- Drama; Truck drivers -- Drama; Automobile rallies -- Drama; Feature films; Car-chase films; Internet videos; Streaming video